Stanley Kubrick at Look Magazine : Authorship and Genre in Photojournalism and Film - Mather, Philippe (Intellect, 2013)
From 1945 to 1950, during the formative years of his career, Stanley Kubrick worked as a photojournalist for Look magazine. Offering a comprehensive examination of the work he produced during this period, Stanley Kubrick at Look Magazine sheds new light on the aesthetic and ideological factors that shaped his artistic voice. Tracing the links between his photojournalism and films, Philippe Mather shows how working at Look fostered Kubrick's emerging talent for combining images and words to tell a story. Mather then demonstrates how exploring these links enhances our understanding of Kubrick's.